A chromosome-length genome assembly and annotation of blackberry (Rubus argutus, cv. “Hillquist”) - Tomáš Brůna; Rishi Aryal; Olga Dudchenko; Daniel James Sargent; Daniel Mead; Matteo Buti; Andrea Cavallini; Timo Hytönen; Javier Andrés; Melanie Pham; David Weisz; Flavia Mascagni; et al. (G3: Genes, Genomes, Genetics, 2022)
AbstractBlackberries (RubusRubusIdaeobatusR. occidentalisR. idaeusR. chingiiRubusR. argutusR. chingiiRubus